2017
DOI: 10.1007/s10753-017-0588-3
|View full text |Cite
|
Sign up to set email alerts
|

Genistein Protects Against Ox-LDL-Induced Inflammation Through MicroRNA-155/SOCS1-Mediated Repression of NF-ĸB Signaling Pathway in HUVECs

Abstract: Genistein plays an important role in the prevention of atherosclerosis. However, the underlying mechanisms have not been fully investigated. In this study, human umbilical vein endothelial cells (HUVECs) were pretreated with genistein (10, 100, and 1000 nM) for 6 h and then exposed to ox-LDL (50 mg/L) for another 24 h. Results showed that ox-LDL induced the expressions of E-selectin, P-selectin, monocyte chemotactic protein-1, interleukin-8, vascular adhesion molecule-1, and intercellular adhesion molecule-1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 51 publications
1
42
0
Order By: Relevance
“…Meanwhile, miR-155 is a main factor for inducing inflammatory responses. 23,24 Thus, AOS also increases antiinflammatory properties of DLD patients by controlling miR-155 level. Hence, all microRNA should be screened in future work to confirm the present results.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, miR-155 is a main factor for inducing inflammatory responses. 23,24 Thus, AOS also increases antiinflammatory properties of DLD patients by controlling miR-155 level. Hence, all microRNA should be screened in future work to confirm the present results.…”
Section: Discussionmentioning
confidence: 99%
“…Genistein was also shown to suppress the production of COX-2 and NO in primary human chondrocytes [32]. Some study indicates that genistein could reverse ox-LDL-induced inflammation through repression of the NF-κB signaling pathway in HUVECs [33]. But so far, studies on the effects of genistein on TMJOA are very limited.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that genistein pretreatment of HUVECs reduces in a dose-dependent manner the oxLDL-induced expressions of E-selectin, P-selectin, MCP-1, IL-8, VCAM-1 and ICAM-1. Further analyses established that the mechanism of action consists of genistein inducing reduction of miR-155 levels and elevation of the suppressor of cytokine signaling 1 (SOCS1) expression that further induces the inhibition of NF-kB signaling pathway in HUVECs [269]. A recent study of Gan et al showed that genistein can inhibit isoproterenol-induced cardiac hypertrophy by increasing miR-451 and the tissue inhibitor of metalloproteinases 2 (TIMP2) expression (a miR-451 target gene), both in vitro in H9C2 embryonic rat cardiomyocytes and in vivo in isoproterenol-induced myocardial hypertrophy in mice [270].…”
Section: Anthocyanidinsmentioning
confidence: 99%